Q: 3x - 4 plus 4x equals 66?

Write your answer...

Submit

Related questions

x = 15 as 4*15+6 = 66 3*15+21 = 66 or an easier way to do it 4x - 3x = 1x 21 - 6 = 15 1x = 15

66 times 6 equals 396.

66 plus 66 equals 132

-66.

There are 2 unknowns

66.

639.

456

62,837,552

3x + 15y = 33 4x - 3y = 66 3x + 15y = 33 divide by 3 to both sides x + 5y = 11 subtract 5y from both sides x = 11 - 5y 4x - 3y = 66, replace x with 11- 5y 4(11 - 5y) - 3y = 66 44 - 20y - 3y = 66 subtract 44 from both sides -23y = 22 divide by -23 to both sides y = -22/23 x = 11 - 5y replace y with -22/23 x = 11 - 5(-22/23) x = 11 + 110/23 x = (11*23 + 110)/23 x = 363/23

26

144

96

144

If I am correct, 9 plus 7 equals 112.

144

144

144, you add the plus numbers, then multiply it by the first.

144, you add the plus numbers, then multiply it by the first.

66

False12x - 66 = 3x + 912x - 3x = 9 + 669x = 65x = 7.22Check:12(7.22) - 60 + 6 = 1(7.22) + 9 + 2(7.22)86.64 - 66 = 7.22 + 9 + 14.4420.64 = 30.66

88+x=3x+22 88=2x+22 66=2x x=33

18 + 10 + 28 + 10 = 66

3x = 66 x = 22

273 13+8 = 21 and 13*21 = 273

Study guides